2015
DOI: 10.1186/s13287-015-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo exposure of bone marrow from chronic kidney disease donor rats to pravastatin limits renal damage in recipient rats with chronic kidney disease

Abstract: IntroductionHealthy bone marrow cell (BMC) infusion improves renal function and limits renal injury in a model of chronic kidney disease (CKD) in rats. However, BMCs derived from rats with CKD fail to retain beneficial effects, demonstrating limited therapeutic efficacy. Statins have been reported to improve cellular repair mechanisms.MethodsWe studied whether exposing CKD rat BMCs ex vivo to pravastatin improved their in vivo therapeutic efficacy in CKD and compared this to systemic in vivo treatment. Six wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Several other drugs also affect EPCs, including erythropoietin-stimulating agents, calcium channel blockers, biguanides without or with thiazolidinedione, and dipeptidyl peptidase-4 inhibitors (49). Drugs, such as pravastatin, rosiglitazone, or coenzyme Q10, improve function and reduce senescence or apoptosis in MSCs (5,90). Last, both EPCs and MSCs release microparticles, which carry genetic and protein cargo.…”
Section: New Treatment Approaches For Progressive Ckdmentioning
confidence: 99%
“…Several other drugs also affect EPCs, including erythropoietin-stimulating agents, calcium channel blockers, biguanides without or with thiazolidinedione, and dipeptidyl peptidase-4 inhibitors (49). Drugs, such as pravastatin, rosiglitazone, or coenzyme Q10, improve function and reduce senescence or apoptosis in MSCs (5,90). Last, both EPCs and MSCs release microparticles, which carry genetic and protein cargo.…”
Section: New Treatment Approaches For Progressive Ckdmentioning
confidence: 99%
“…Autologous therapy should thus be considered for these patients-provided that disease-induced dysfunction is not present. Preclinical studies show a pronounced reduction in vascular regenerative effects of BM mononuclear cells of donors with cardiovascular disease (CVD), including CKD [16]. In culture-expanded MSCs, the effect of CVD is less clear, with conflicting reports depending on the cardiovascular disease (model) and little information available for CKD [17].…”
Section: Introductionmentioning
confidence: 99%
“…There were preliminary indications that the paracrine function might not be preserved in CKD. Progenitor cells in experimental CKD display an altered paracrine profile, including reduced expression of vascular endothelial growth factor (VEGF) and reduced migration towards chemotactic stimuli [16,36]. Furthermore, in vitro studies have shown that a uremic environment negatively affects progenitor cell function [37,38].…”
mentioning
confidence: 99%
“…Drugs or interventions that may improve function and reduce senescence or apoptosis in MSC include hypoxic and other preconditioning measures 166168 , pravastatin 169 , rosiglitazone 170, 171 or coenzyme Q10 172 therapies, and epigenetic regulation 173, 174 . Both preconditioned MSC and EPC have shown improved cell survival, homing to injured sites, and paracrine activities.…”
Section: Introductionmentioning
confidence: 99%